The non continuity of the vaccination schedule for children registered in the family health strategy units - Cavalcante, Anne Karoliny Morais; de Paula, Weslla Albuquerque; Quirino, Carla Andréa da Silva; Souza, Gabrielly Laís de Andrade; Almeida, Samira Maria Oliveira (Revista de Enfermagem UFPE on line, 2015)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–> ABSTRACT <p class="MsoNormal" style="margin-top: 1.0pt; margin-right: 0cm; margin-bottom: 1.0pt; margin-left: 0cm; text-align: justify; line-height: normal; background: white; border: none; mso-border-bottom-alt: solid windowtext 2.25pt; padding: 0cm; mso-padding-alt: 0cm 0cm 1.0pt 0cm;">Objective: identifying the factors associated to non-continuity of the vaccination schedule in children under 1 year old. Method: an exploratory, cross-sectional, descriptive and of a quantitative approach carried out from January to March 2012. The sample included 130 mothers/ caretakers of children under one year old. The data collection instrument consisted of 28 questions. The research project was approved by the Research Ethics Committee, Protocol 167/11. Results: it was found in the interviews that the responsible for leading the child to the FHS was 100% female figure, where most were aged between 19-33 years old (58,46%), married (74,62) and of home (61,54%). The lack of immunobiological in the unit was responsible for 35,38% of the difficulties encountered by mothers/caregivers to vaccinate the child. Conclusion: the factors associated with non-vaccination are: the low maternal education, the lack of knowledge of them about the real importance of vaccination and low family income. Descriptors: Vaccination; Family Health Program; Nursing; Immunization Programs; Public Policies. RESUMO <p class="MsoNormal" style="margin-top: 1.0pt; margin-right: 0cm; margin-bottom: 1.0pt; margin-left: 0cm; text-align: justify; line-height: normal; background: white; border: none; mso-border-bottom-alt: solid windowtext 2.25pt; padding: 0cm; mso-padding-alt: 0cm 0cm 1.0pt 0cm;">Objetivo: verificar os fatores associados a não continuidade do esquema vacinal em crianças menores de 1 ano. Método: estudo exploratório, transversal, descritivo, de abordagem quantitativa, realizado no período de janeiro a março de 2012. A amostra compreendeu 130 mães/cuidadoras de crianças menores de um ano. O instrumento de coleta de dados foi composto por 28 perguntas. O projeto de pesquisa foi aprovado pelo Comitê de Ética em Pesquisa, Protocolo 167/11. Resultados: verificou-se nas entrevistas que o responsável por conduzir a criança até a ESF foi 100% a figura feminina, onde a maioria possuía faixa etária entre 19 a 33 anos (58,46%), eram casadas (74,62) e do lar (61,54%). A falta de imunobiológico na unidade foi responsável por 35,38% das dificuldades encontradas pelas mães/cuidadoras para vacinar a criança. Conclusão: os fatores associados a não vacinação são: a baixa escolaridade materna, falta de conhecimento das mesmas sobre a importância real da vacinação e a baixa renda familiar. Descritores: Vacinação; Programa Saúde da Família; Enfermagem; Programas de Imunização; Políticas Públicas. RESUMEN <p class="MsoNormal" style="margin-top: 1.0pt; margin-right: 0cm; margin-bottom: 1.0pt; margin-left: 0cm; text-align: justify; line-height: normal; mso-pagination: none; background: white; mso-layout-grid-align: none; text-autospace: none; border: none; mso-border-bottom-alt: solid windowtext 2.25pt; padding: 0cm; mso-padding-alt: 0cm 0cm 1.0pt 0cm;">Objetivo: identificar los factores asociados a la no continuidad del programa de vacunación en niños menores de 1 año de edad. Método: un estudio exploratorio, transversal, descriptivo y de enfoque cuantitativo realizado entre enero y marzo de 2012. La muestra incluyó a 130 madres/ cuidadores de niños menores de un año. El instrumento de recolección de datos consistió en 28 preguntas. El proyecto de investigación fue aprobado por el Comité de Ética en la Investigación, Protocolo 167/11. Resultados: se encontró en las entrevistas que el responsable de dirigir al niño a la ESF fue del 100% la figura femenina, donde la mayoría tenía entre 19 a 33 años (58,46%) estaban casadas (74,62) y del hogar (61,54%). La falta de inmunobiológicos en la unidad era responsable de 35,38% de las dificultades encontradas por las madres/cuidadores para vacunar a los niños. Conclusión: los factores asociados con la no vacunación son la baja educación materna, la falta de conocimiento de las mismas sobre la verdadera importancia de la vacunación y los bajos ingresos familiares. Descriptores: Vacunación; Programa Salud de la Familia; Enfermería; Programas de Inmunización; Políticas Públicas. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>